Exploring alternative economic pathways: a comparison of foundational economy and Doughnut economics. Issue 1 (9th December 2022) - Wahlund, Madeleine; Hansen, Teis
Abstract: A number of intersecting crises are currently ongoing at multiple scales, including increasing inequality, environmental degradation, and climate destabilization, as well as new surges of populism and mounting public health threats. These emergencies question our economic model of past decades and provoke a rethinking of the general approach to economic policy from a multi-scalar perspective. In this article, we compare two approaches aiming to rethink economic development policy: foundational economy and Doughnut economics, and consider if and how they complement each other. We conclude that the two approaches are potentially complementary, most prominently in their call for high-income countries to refocus from growth per se to purpose-driven economic strategies that prioritize public services and redistribute incomes. However, they differ in respect to their geographical focus, environmental concerns, and application. To properly address tradeoffs between social needs and environmental effects, foundational scholarship would benefit from deeper engagement with the socioenvironmental perspective presented in Doughnut economics, which stresses the need to consider human-nature interlinkages. In sum, combining different aspects of the two approaches promises to provide a more robust response to contemporary challenges, especially for local policy making.